Association of recent antibiotic exposure and coronary artery lesions in Kawasaki disease: nationwide study - Ansai, Hideto; Yamada, Masaki; Masuda, Hiroshi; Imadome, Ken-Ichi; Yashiro, Mayumi; Noval Rivas, Magali; Arditi, Moshe; Nakamura, Yosikazu; Abe, Jun (Frontiers in Pediatrics, 2024)
To investigate the relationship between recent antibiotic exposure and the development of coronary artery lesions (CALs) during the clinical course of Kawasaki disease (KD).Data were obtained from the 25th nationwide epidemiological survey of KD conducted in Japan from 2017 to 2018. Baseline characteristics and clinical course were compared between Antibiotics (+) and Antibiotics (-) groups.Nationwide survey of KD in Japan.KD patients were enrolled by response to a questionnaire sent to physicians working in pediatrics at hospitals with >100 beds.Antibiotic exposure within one week before the first hospital visit as KD patients.The relationship between recent antibiotic exposure and the development of coronary artery lesions (CALs).Out of 28,265 KD patients, 12,918 (45.7%) received antibiotics. In KD patients who received antibiotics in the week before KD diagnosis, the frequency of coronary artery lesions (CALs) at each phase were significantly higher compared to those who did not receive antibiotics.In further analysis using propensity score matching, recent antibiotic exposure and the initial IVIG resistance were associated with CALs at the acute and the sequelae phase. After adjusting for the status of initial IVIG resistance, recent antibiotic exposure remained associated with CALs during the acute phase (adjusted OR 1.29, 95%CI 1.16, 1.43) and the sequelae phase (1.26, 95%CI 1.04, 1.52).These observations suggest that recent antibiotic exposure might be associated with higher frequency of CAL development in KD patients, possibly by altering the gut microbiota and diminishing beneficial bacteria.